Problemas de aprendizaje y su incidencia en el proceso de enseñanza online, generado por la pandemia del covid -19 reflexionando desde la Carrera de Educación Básica de F.C.J.S.E. – UTB, cantón Babahoyo, Provincia de Los Ríos - Valero Tierra, Pedro Enrique (2020)
This case study was developed in order to analyze the incidence of learning problems in the online teaching process, generated by the Covid -19 pandemic, reflecting on the basic education career of F.C.J.S.E. - UTB, Babahoyo canton, Los Ríos province. A descriptive-explanatory research study of documentary-bibliographic modality is proposed, the interview was used, where it was evidenced that children and parents present difficulties in the adaptability of online classes, therefore the child's learning is low , not having access to the internet is one of the problems in addition to the fact that children are burdened with too much work, there is little time for teachers and explaining the classes in 40min of tutorials is almost impossible to teach, before this the parents take the role of educators, it was evidenced that teachers do not support parents by indicating the ways in which their children can learn, the rhythm of online learning is different from the structure of a normal day in relation to the home, in this modality economic inequality is highlighted families live, unfortunately many children do not have the technology or the environment necessary to meet academic expectations. Therefore, it is concluded that the online teaching process affects the learning problems of students, causing poor performance and school failure.